A Study of Polynomials of the First kind Pafnuty Chebyshev - Hashemi, Jawid; Sediqy, Abdul Wares (Farah Research and Scientific Journal, 2025)
The first kind of Chebyshev polynomials, known as the Pafnuty Chebyshev polynomials, are recognized as one of the most important types of Chebyshev polynomials, playing a fundamental role in mathematics and computer science. These polynomials are particularly significant due to their unique characteristics, which make them important in data analysis and numerical problem-solving. Polynomials, especially in estimating functions and solving differential equations, are recognized as effective tools for reducing errors and improving computational accuracy. The history of Chebyshev polynomials dates back to the time of the prominent Russian mathematician Pafnuty Chebyshev and the early days of mathematics. Since then, their applications have developed in various fields, particularly in numerical analysis and signal processing. The importance of the first kind of Chebyshev polynomials lies in their ability to create accurate approximations and their orthogonality in functional space. These polynomials are employed in numerical methods such as frequency analysis, integration, and function estimation. In this paper, we examine and analyze the first kind of Chebyshev polynomials using both analytical and numerical methods. We first collected definitions and characteristics of these polynomials from reputable sources, then analyzed their mathematical properties, which include recurrence relations and algebraic features. Data were extracted from books, research articles, and credible internet sources, and analyzed using mathematical methods. The results of this research indicate that these polynomials, due to their specific characteristics in mathematics and applied sciences, are highly efficient in function approximation and solving various mathematical problems.